Global incorporation of meta-fluorotyrosine or meta-fluorophenylalanine into 1,2-catechol dioxygenase modulates the binding affinities of substrates - Wong, Michael C. H.; Grant, Thomas E.; Karbalaei-Heidari, Hamid Reza; Robotham, Anna C.; Loewen, Matthew E.; St-Jacques, Antony D.; Budisa, Nediljko; Loewen, Michele C. (Frontiers in Synthetic Biology, 2024)
Previous studies have shown how replacing canonical residues with isosteric amino acid analogs in enzymes can predictably alter biocatalytic activities by introducing variations in the first and second shell residues relative to the binding pocket. In this study, we explore the global integration of amino acid analogs into 1,2-catechol dioxygenase from Rhodococcus opacus (Rho 1,2-CTD), an industrial enzyme containing non-heme iron that is vital for phenol ring degradation. Methods: We replaced tyrosine residues in the first shell of the binding pocket, phenylalanine residues in the second shell, and methionine residues near the binding pocket with m-fluorotyrosine (m-FY), m-fluorophenylalanine (m-FF), and Nle, respectively, using auxotrophic Escherichia coli strains. Results: The expression, purification and incorporation of m-FY and m-FF into the Rho 1,2-CTD was successful, while the Nleinsertion did not work. The structural characterization of the resulting m-FF-and m-FYcontaining variants provided a mechanistic framework and a plausible explanation for the results of the kinetic analyses of the native enzyme and fluorinated variants. Discussion: Our findings demonstrate the impact of fluorination on the activity of 1,2-catechol dioxygenase, revealing its influence on residues near the substrate (first shell) as well as those distant from the binding pocket (second shell). This provides a robust foundation for future activity engineering efforts.